Comprehensive Management of Helicobacter pylori Infection - Abdul Ghaffar Hamzah; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Helicobacter pylori (Hp) infection is a chronic gram-negative bacterial infection, that infects the epithelium of the stomach. This prevalence is very high and varies depending on factors such as geographical location, ethnicity, age, and socioeconomic. The key management of Hp infection is accurate diagnosis and treatment. The H. pylori diagnostic examination consists of non-invasive and invasive tests, the most common non-invasive tests are serological tests, urea breath tests (UBT), and stool antigen tests, while invasive tests are rapid urease tests, histopathology, culture, and PCR. The goal of H. pylori eradication is to heal peptic ulcers and reduce the risk of gastric cancer. Eradication therapy that is recommended worldwide and used in Indonesia is the triple drug combination therapy consisting of a PPI, clarithromycin and amoxicillin or metronidazole for 14 days. The success of eradication therapy is highly dependent on the choice of therapeutic regimen, patient compliance in taking multi-drugs with possible drug side effects, and the sensitivity of H. pylori strains to the antibiotics consumed.